Gambaran Tingkat Pengetahuan Remaja Putri tentang Anemia di SMAN 8 Kota Jambi dan SMPN 11 Kota Jambi - Serigar, Melanie Putria Dewita; Wulansari, Arnati; Hesty, Hesty (3031-8572, 2024)
Adolescence is a period of development from childhood to adulthood that lasts between the ages of 10 and 19. Adolescent girls are a group of adolescents who are prone to anaemia compared to male adolescents, especially adolescent girls who experience menstruation every month. According to WHO, the prevalence of anaemia in women aged 15-49 years is 30%. According to Riskesdas, the prevalence of anaemia in the 15-24 age group was 5,671 or about 32%. Based on data from the Jambi City Health Office, there are 88 people with anaemia among adolescents aged 15-18 years. The purpose of this study was to determine the level of knowledge about anaemia among adolescent girls in SMAN 8 Jambi City and SMPN 11 Jambi City. This study is a quantitative study with analytical descriptive design. The number of respondents in this study were 93 respondents from SMAN 8 Jambi City and 90 respondents from SMPN 11 Jambi City. This research was conducted from March to May 2024. The sample in the study was taken using proportional random sampling technique. Data collection was done by filling a questionnaire and the research data was analysed univariately. The results showed that most of the female adolescent respondents with less knowledge about anaemia were 86 people (47%). The average score of anaemia knowledge of high school girls is 31 (33.3%) or still in the category of lack of knowledge and the average score of anaemia knowledge of junior high school girls is also almost the same as the average score of knowledge of high school girls which is 30 (33.3%). It can be concluded from this study that most (47%) of the respondents have less knowledge about anaemia. Adolescent girls are expected to increase their knowledge and understanding about anaemia in order to prevent anaemia in adolescent girls.